2011
DOI: 10.1210/en.2010-1132
|View full text |Cite
|
Sign up to set email alerts
|

Fragments of Genomic DNA Released by Injured Cells Activate Innate Immunity and Suppress Endocrine Function in the Thyroid

Abstract: Activation of innate and acquired immune responses, which can be induced by infection, inflammation, or tissue injury, may impact the development of autoimmunity. Although stimulation of cells by double-stranded DNA (dsDNA) has been shown to activate immune responses, the role of self-genomic DNA fragments released in the context of sterile cellular injury is not well understood. Using cultured thyroid cells, we show that cell injury prompts the release of genomic DNA into the cytosol, which is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…The observation of increased buds at the nuclear envelope in Dnase2a-deficient cells may thus indicate a higher rate of damaged DNA generation than removal. Nevertheless, other studies have detected DNA fragments arising from replication in budding yeast (Sogo et al, 2002) and fly (Blumenthal and Clark, 1977), over represented dsDNA fragments from chromosomes as free dsDNA molecules in human cells during S phase (Gomez and Antequera, 2008), and release of short DNA fragments into the cytosol prompted by physical (Kawashima et al, 2011) or radiation-induced injury (Pang et al, 2011). Interestingly, unrepaired or irreparable DNA has been found to re-localize to the nuclear periphery (Nagai et al, 2008; Oza et al, 2009), suggesting that it may be segregated from replicating DNA for clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of increased buds at the nuclear envelope in Dnase2a-deficient cells may thus indicate a higher rate of damaged DNA generation than removal. Nevertheless, other studies have detected DNA fragments arising from replication in budding yeast (Sogo et al, 2002) and fly (Blumenthal and Clark, 1977), over represented dsDNA fragments from chromosomes as free dsDNA molecules in human cells during S phase (Gomez and Antequera, 2008), and release of short DNA fragments into the cytosol prompted by physical (Kawashima et al, 2011) or radiation-induced injury (Pang et al, 2011). Interestingly, unrepaired or irreparable DNA has been found to re-localize to the nuclear periphery (Nagai et al, 2008; Oza et al, 2009), suggesting that it may be segregated from replicating DNA for clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Several underlying mechanisms may explain its action: redundant ROS generated during trapping, oxidation and organification of excessive iodine in thyrocytes (likely due to a defect in the iodine processing machinery) can lead to elevated oxidative stress and consequential oxidative cell damage. This damage may stimulate thyrocytes as danger (or damage)-associated molecular patterns to produce and secrete cytokines and chemokines, thus recruiting lymphocytes to the thyroid [98,99,100], where they meet major thyroid auto-antigens, including thyroglobulin. Modification by excessive iodine may alter the conformation of the thyroglobulin molecule to facilitate its antigen presentation by professional antigen presenting cells, as well as MHC-expressing thyrocytes and its recognition by T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to exogenous PAMPs, DAMPs are endogenous intracellular and extracellular molecules (such as genomic DNA fragments, heat shock proteins, collagen and hyaluronic acid) released from sterile cells damaged by various stimuli, such as ischemia/reperfusion injury, trauma and oxidative stress [98]. Our group has reported that genomic DNA fragments released from injured rat thyroid cells can be recognized by extrachromosomal histone H2B, leading to the activation of both innate and acquired immune responses in thyroid cells and the suppression of thyroid function, suggesting that thyroid tissue injury is a potential trigger for autoimmune reaction and the induction of thyroid dysfunction [99]. Moreover, stimulation of double-stranded RNA (a typical DAMP) significantly increased the expression of interferon-responsive genes, cytokines and chemokines and suppressed thyroid functional gene expression in cultured human thyroid cells [100].…”
Section: Mechanisms Involved In Iodine-induced Autoimmune Thyroiditismentioning
confidence: 99%
“…These findings indicated that stress signaling cascades were involved although it remains unclear whether oxidative stress alone or cell-specific signaling molecules induced such apoptosis. Either way, these findings indicate that neutral TSHR-mAbs have an ability to aggravate the local inflammatory infiltrate within the thyroid by inducing cellular apoptosis; a phenomenon known to activate innate and bystander immune-reactivity via DNA release from the apoptotic cells [62]. This phenomenon may also be involved in Graves’ orbitopathy via activation-induced fibroblast death, since these cells express TSHR abundantly (see below).…”
Section: Thyrocyte Oxidative Stress and Apoptosis Induced By Tshr Antmentioning
confidence: 99%